Dentes de Amniotas da Laje do Coringa (Formação Alcântara, albo-cenomaniano da bacia de São Luís-Grajaú): Identificação, descrição, aspectos paleobiológicos, biocronológicos, paleogeográficos e paleobiogeográficos - Elias, Felipe Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
A utilização de dentes isolados, com finalidades taxonômicas, é reconhecida por diversos autores. No Hemisfério Norte investigações desta natureza são freqüentes, versando principalmente sobre micro e macromorfologias dentárias e sua utilização na identificação de grupos taxonômicos, eventualmente a categorias bastante específicas. No Hemisfério Sul, em especial no Brasil, estudos enfocando dentes isolados ainda representam uma parcela bastante sutil de contribuição no âmbito da Paleontologia. Esta contribuição representa o plano de investigação de um conjunto de dentes de amniotas, resgatados em um dos mais ricos e diversificados depósitos fossilíferos cretácicos do Estado do Maranhão: o afloramento Laje do Coringa. Situado na Ilha do Cajual, Município de Alcântara, representa um bone-bed com expressivo registro fossilífero do neo-Albiano/eo-Cenomaniano da Formação Alcântara, Bacia de São Luís- Grajaú. Considerando sua abundância e diversidade morfológica, os dentes fósseis dos depósitos cretácicos no Estado do Maranhão mostram-se potencialmente importantes no âmbito de investigações paleontológicas. A análise de parâmetros morfológicos aplicados à coroa, permitiu a identificação de 19 morfótipos dentários, representando terópodos (Carcharodontosauridae, Spinosauridae e Velociraptorinae), saurópodos (Titanosauria e Diplodocoidea), crocodilomorfos (Pholidosauridae) e pterossauros (Anhangueridae e Ornithocheiridae). A variedade morfológica evidenciada na amostra da Laje do Coringa sugere uma relativa diversidade paleobiológica e paleoecológica durante o neo-Albiano/eo- Cenomaniano do Estado do Maranhão... .

The use of isolated tooth, with taxonomic purposes, is recognized for many authors. In North Hemisphere inquiries of this nature are frequent, mainly treating about dental micro and dental macromorphologies and its use in the identification of taxonomic groups, eventually the very specific categories. In South Hemisphere, in especially Brazil, studies focusing isolated teeth still represent a very subtle parcel of contributions in the scope of Paleontology. This contribution represents the plan of inquiry of a amniotes teeth's set, rescued in one of richest and diversified Cretaceous fossiliferos deposits of the Maranhão State: the Laje do Coringa outcrop. Situated in the Cajual Island, Alcântara Municipality, it represents a bone-bed with expressive fossiliferous record in the late Albian/early Cenomanian of the Alcântara Formation, São Luís-Grajaú Basin. Considering its abundance and morphologic diversity, fossil teeth of the Cretaceous deposits in the Maranhão State reveal potentially important in the scope of paleontological inquiries. The analysis of morphologic parameters applied to the dental crown allowed the identification of 19 dental morphotypes, representing theropods (Carcharodontosauridae, Spinosauridae and Velociraptorinae), sauropods (Titanosauria and Diplodocoidea), crocodilomorphs (Pholidosauridae) and pterosaurs (Anhangueridae and Ornithocheiridae). The morphologic variety evidenced in the sample of the Laje do Coringa outcrop suggests a relative paleobiological and paleoecological diversity during the late Albian/early Cenomanian of the Maranhão State. As evidenced in studies developed for other authors (and confirmed in this inquiry) the paleofaunistical assemblage of the Alcântara Formation probably had a particular similarity with isochronous assemblages of the North of Africa, suggesting that the events of biological particularity in each one of continental... (Complete abstract, click electronic address below).
Keywords: Paleontologia; Grupo Itapecuru; Dentes isolados; Neo-Cretáceo; São Luís-Grajaú basin; Itapecuru Group; Alcântara formation; Isolated teeth; Late Albian/early Cenomanian; Late Cretaceous